Acute Pyelonephritis in a Dog: A Case Report - Kar, Payel; Rajesh, J B; Das, Manas; Kar, Debalina (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Plonephritis describes inflammation of the renal pelvis as  Well as adjacent renal parenchyma. Although ascending  infection of the lower urinary tract (LUT) is the primary cause  of most episodes of pyelonephritis, hematogenous spread of  infection can also occur but less frequently. The disease can  be acute or chronic, and unilateral or bilateral (Parry, 2005).  About 75% of infections are caused by a single bacterial  pathogen; 20% of UTIs are caused by two coinfecting species;  and roughly 5% are caused by three species (Olin andBartges,  2015). In both dogs and cats, the bacteria that most frequently  result in UTIs are Escherichia coli, Staphylococcus, and various  others like Proteus, Klebsiella, Pasteurella, Pseudomonas,  Corynebacterium, and several more infrequently reported  genera (Ling et al., 2008).
Keywords: Acute; Pyelonephritis; Dog